Catalogue of the Collection of Parchments of the Saint Lazarus Hospital of Coimbra (1197-1723) - Queirós, Abílio (2016)
In the documentary fund of the Saint Lazarus Hospital in Coimbra (originally called Gafaria of Coimbra) at the Archive of the University of Coimbra, there is gathered a collection of parchments which will be published in the present work. Their catalog has been produced, permitting, by means of that tool of documentary description, that each one of the 121 parchments which form this collection (dated from 1197 to 1723) can be known. Among the various documentary typologies the Contracts of rental agreement stand out considerably, as well as the Royal Letters from D. Afonso IV, D. Fernando, D. João I, D. Afonso V and D. João V, but also the Donation Letters giving out goods to the Hospital (on account of their leprous patients), the Letters of Purchase and Sale, and several Sentences given by various judges from Coimbra and other jurisdictions.http://dx.doi.org/10.14195/2182-7974_29_1